Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0191152
|View full text |Cite
|
Sign up to set email alerts
|

Influence of multiplicative stochastic variation on translational elongation rates

Abstract: Experimental data indicate that stochastic effects exerted at the level of translation contribute substantially to the variation in abundance of proteins expressed at moderate to high levels. This study analyzes the theoretical consequences of fluctuations in residue-specific elongation rates during translation. A simple analytical framework shows that rate variation during elongation gives rise to protein production rates that consist of sums of products of random variables. Simulations show that because the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 83 publications
(161 reference statements)
0
9
0
Order By: Relevance
“…This system of cotranslational insertion has been theoretically studied using the Totally Asymmetric Exclusion Process (TASEP) framework [26]. This model is also one of the many that study ribosome dynamics on the mRNA, making use of the TASEP framework [22,25,27,29]. The framework, in general, models unidirectional stochastic motion of particles on a onedimensional lattice.…”
Section: Translation Model and Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…This system of cotranslational insertion has been theoretically studied using the Totally Asymmetric Exclusion Process (TASEP) framework [26]. This model is also one of the many that study ribosome dynamics on the mRNA, making use of the TASEP framework [22,25,27,29]. The framework, in general, models unidirectional stochastic motion of particles on a onedimensional lattice.…”
Section: Translation Model and Theoretical Backgroundmentioning
confidence: 99%
“…Several experimental studies are now looking at how the individual components of translation affect and aid protein synthesis [15][16][17][18][19][20][21]. These studies have also inspired several modeling frameworks that look at mRNA translation as a whole [22][23][24][25][26][27][28], effects of the assembly of the ribosomal machinery [25,29] or protein expression bursts as a result of stochastic transcription and translation [2,4,11,[30][31][32][33][34][35][36][37][38][39][40]. In this work, we focus on the kinetic aspects of mRNA translation.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, in the thermal bath of the eukaryotic nucleus, or prokaryotic nucleoid, molecular motion is random and the behavior of a molecule can only be described in probabilistic terms ( 8 , 9 ). Single-molecule experimentation allows fluctuation analysis ( 10–12 ) and has revealed very heterogeneous behavior of molecules ( 13–18 ). Measurements have shown that protein-mediated loops form and rupture stochastically, and the lifetimes of such loops span several orders of magnitude ( 19–22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, in the thermal bath of the eukaryotic nucleus, or prokaryotic nucleoid, molecular motion is random and the behavior of a molecule can only be described in probabilistic terms (Nelson, 2003;Phillips R. et al, 2013). Single-molecule experimentation allows fluctuation analysis (Bido et al;Kundu et al, 2020;Milenkovic et al, 2020) and has revealed the robustly heterogeneous looping behavior of molecules (Datta and Seed, 2018;Finzi and Gelles, 1995;Graham et al, 2017;Kumar et al, 2016;Manzo et al, 2011;Manzo et al, 2012;Miyashita et al, 2015;Neuman et al, 2003;Wang et al, 1998;Zurla, 2009). Indeed, protein-mediated loops form and rupture stochastically in purified systems, and the lifetimes of such loops span several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, in the thermal bath of the eukaryotic nucleus, or prokaryotic nucleoid, molecular motion is random and the behavior of a molecule can only be described in probabilistic terms (6,7). Single-molecule experimentation allows fluctuation analysis (8)(9)(10) and has revealed very heterogeneous looping behavior of molecules (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Measurements have shown that protein-mediated loops form and rupture stochastically, and the lifetimes of such loops span several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%